Experimental Observation of a Nearly Logarithmic Decay of the Orientational Correlation Function in Supercooled Liquids on the Picosecond-to-Nanosecond Time Scales - Cang, Hu; Novikov, V. N.; Fayer, M. D. (Physical review letters, 2003)
Dynamics of five supercooled molecular liquids have been studied using optical heterodyne detected optical Kerr effect experiments. "Intermediate" time scale power law decays (approximately 2 ps to 1-10 ns) with temperature independent exponents close to -1 have been observed in all five samples from high temperature to approximately T(c), the mode-coupling theory (MCT) critical temperature. The amplitude of the intermediate power law increases with temperature as [(T-T(c))/T(c)](1/2). The results cannot be explained by standard MCT, and one possible explanation within MCT would require the higher order singularity scenario, thought to be highly improbable, to be virtually universal.